2007
DOI: 10.1146/annurev.pharmtox.47.120505.105225
|View full text |Cite
|
Sign up to set email alerts
|

Diseases Caused by Defects in the Visual Cycle: Retinoids as Potential Therapeutic Agents

Abstract: Absorption of a photon by an opsin pigment causes isomerization of the chromophore from 11-cisretinaldehyde to all-trans-retinaldehyde. Regeneration of visual chromophore following light exposure is dependent on an enzyme pathway called the retinoid or visual cycle. Our understanding of this pathway has been greatly facilitated by the identification of disease-causing mutations in the genes coding for visual cycle enzymes. Defects in nearly every step of this pathway are responsible for human-inherited retinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
458
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 370 publications
(464 citation statements)
references
References 210 publications
(222 reference statements)
4
458
1
1
Order By: Relevance
“…Patients suffering from diseases affecting the visual cycle, such as Stargardt's dystrophy, Best disease, or Oguchi disease, should require extra care as they might suffer increased susceptibility to light damage, as was found in animal models. 7,32 Continued research on photochemical damage is relevant because many open questions remain, only some of them treated in this limited review. An action spectrum for freely moving animals exposed to continuous light for one or more natural days, thus in the 'Noell conditions', is still lacking, and the search for the photosensitizers underlying the Ham-type action spectrum is far from complete.…”
Section: Eyementioning
confidence: 99%
“…Patients suffering from diseases affecting the visual cycle, such as Stargardt's dystrophy, Best disease, or Oguchi disease, should require extra care as they might suffer increased susceptibility to light damage, as was found in animal models. 7,32 Continued research on photochemical damage is relevant because many open questions remain, only some of them treated in this limited review. An action spectrum for freely moving animals exposed to continuous light for one or more natural days, thus in the 'Noell conditions', is still lacking, and the search for the photosensitizers underlying the Ham-type action spectrum is far from complete.…”
Section: Eyementioning
confidence: 99%
“…In Drosophila, defects in the generation of the chromophore cause profound reductions in opsin levels [71], while this is not the case in vertebrate rods and cones [72]. It has been suggested that the chromophore accelerates opsin maturation by facilitating deglycosylation and transport of the opsin [73,74].…”
Section: Maturation Of Rhodopsinmentioning
confidence: 99%
“…Vitamin A (all-trans retinol) is subsequently transported to the retinal pigment cells where it is converted to the chromophore through a process dependent on the PINTA retinoid-binding protein and the NINAG oxidoreductase. The chromophore is transported to the photoreceptor cells where it binds to the opsin resulting in the generation of rhodopsin pigment epithelium (RPE) [72], it appears that Drosophila retinal pigment cells are the closest functional equivalent to the RPE. The ninaG gene encodes an oxidoreductase, which is proposed to act in the conversion of (3R)-3hydroxyretinol to the 3S enantiomer in the compound eye [82,83].…”
Section: Maturation Of Rhodopsinmentioning
confidence: 99%
“…Disease is typically associated with the production of harmful gene products that promote pathology by inhibiting critical pathways resulting in cell death. [24][25][26] Strategies to prevent photoreceptor death during retinal degenerative disease such as gene replacement therapies or inhibition of cell death pathways have been undertaken with some success; [27][28][29] however, effective treatments for these blinding disorders are lacking.…”
mentioning
confidence: 99%